Seismic sedimentology of lower part of second member of Shanxi Formation in Gaojiahe area, Ordos Basin - Shenghua LAI; Pu BAI; Chao YE; Lei ZHANG; Jing CHI (Shiyou shiyan dizhi, 2020)
The method of using seismic information to study the planar distribution characteristics of sedimentary system is illustrated using the lower part of the second member of the Lower Permian Shanxi Formation in the Gaojiahe 3D area of the Ordos Basin as an example. Firstly, based on rock physical properties, time-frequency scanning technology was used to study the seismic reflection characteristics of coal seams in a 90° phase seismic data volume. Secondly, by designing specific filters, seismic waves were filtered to suppress the influence of coal seams on seismic reflection characteristics. A fine (high-frequency) isochronous stratigraphic framework in the 3D seismic data volume was created by combining high-precision sequence stratigraphy with seismic sedimentology. Finally, combining geological features, logging responses and seismic facies analysis, provided the sedimentary analysis of isochronous stratigraphic slices with different frequencies. Mixed frequency display technology was applied to study the spatial distribution characteristics of sedimentary facies. The distributary channels in the lower delta plain sub-facies of the second member of Shanxi Formation in the Gaojiahe 3D area are mainly represented by three trends: (1) Some show north-south, east-west, and then north-south trends, along S229, S228, S232, S208, Y124 well edge. In these distributary channels, a meandering beach with a certain scale may develop near well S231. (2) Some show a northwest-southeast trend, mainly distributed along wells S212, Y127, and S209; (3) Some show a nearly west trend. A large-scale lateral river migration zone develops along wells S210 and S226.